Stewardship and health systems strengthening: An overview. (24th January 2019) - Brinkerhoff, Derick W.; Cross, Harry E.; Sharma, Suneeta; Williamson, Taylor
Summary: The World Health Organization (WHO) introduced the concept of stewardship to clarify the practical components of governance in the health sector. For the WHO, stewardship concentrated on how government actors take responsibility for the health system and the wellbeing of the population, fulfill health system functions, assure equity, and coordinate interaction with government and society. This article overviews the contents of this special issue, which offers examples of how health stewards in a variety of countries have addressed issues of health security, primary care expansion, family planning, and quality of care. The contributors' articles draw lessons for policy, programs, and management useful for practitioners and scholars. Our overview identifies several themes emerging from the articles: the foundational role of legal frameworks for effective stewardship, the importance of institutional arrangements as enablers, the influence of regional and global entities on national stewardship, the connection between credible decision‐making structures and stewardship, and pathways to sustainable financing and domestic resource mobilization. The discussion concludes with highlighting several gaps in knowledge and practice related to health stewardship.